2000
DOI: 10.1038/35010121
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane phosphoprotein Cbp regulates the activities of Src-family tyrosine kinases

Abstract: The Src family of protein tyrosine kinases (Src-PTKs) is important in the regulation of growth and differentiation of eukaryotic cells. The activity of Src-PTKs in cells of different types is negatively controlled by Csk, which specifically phosphorylates a conserved regulatory tyrosine residue at the carboxy-terminal tail of the Src-PTKs. Csk is mainly cytoplasmic and Src-PTKs are predominantly membrane-associated. This raises a question about the mechanism of interaction between these enzymes. Here we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
518
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 493 publications
(536 citation statements)
references
References 17 publications
16
518
2
Order By: Relevance
“…For example, the cytoskeletal-associated protein, paxillin, recruits Csk to the focal adhesion sites for the regulation of cell migration (Schaller and Parsons, 1995), whereas the signalling protein, Dok-1, induces Csk translocation to the plasma membrane for mitogenic regulation (Zhao et al, 2006). Additional Csk-binders have been identified, including the structural protein of caveolae, caveolin-1 (Lee et al, 2000), the junctional proteins VE-cadherin (Baumeister et al, 2005) and ZO-1 and the transmembrane protein phosphoprotein associated with glycosphingolipidenriched microdomain (PAG)/Csk-binding protein (Cbp) (Brdicka et al, 2000;Kawabuchi et al, 2000) localized in cholesterol-enriched membrane domains or rafts (named PAG in this study). Interestingly, SFK phosphorylation of these proteins triggers their binding to Csk through a SH2-pTyr-dependent mechanism, which creates a negative feedback regulatory loop.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the cytoskeletal-associated protein, paxillin, recruits Csk to the focal adhesion sites for the regulation of cell migration (Schaller and Parsons, 1995), whereas the signalling protein, Dok-1, induces Csk translocation to the plasma membrane for mitogenic regulation (Zhao et al, 2006). Additional Csk-binders have been identified, including the structural protein of caveolae, caveolin-1 (Lee et al, 2000), the junctional proteins VE-cadherin (Baumeister et al, 2005) and ZO-1 and the transmembrane protein phosphoprotein associated with glycosphingolipidenriched microdomain (PAG)/Csk-binding protein (Cbp) (Brdicka et al, 2000;Kawabuchi et al, 2000) localized in cholesterol-enriched membrane domains or rafts (named PAG in this study). Interestingly, SFK phosphorylation of these proteins triggers their binding to Csk through a SH2-pTyr-dependent mechanism, which creates a negative feedback regulatory loop.…”
Section: Introductionmentioning
confidence: 99%
“…A current model for the role of Lyn infers that COOH-terminal Src kinase (Csk) negatively regulates Lyn by phosphorylating the COOH-terminal negative regulatory tyrosine at position 507 (Y-507) (19). In contrast, a membrane protein tyrosine phosphatase, CD45, positively regulates Lyn by dephosphorylating Y-507, which causes a conformational change that reveals the catalytic domain of Lyn and promotes autophosphorylation of the positive regulatory tyrosine at position 396 (Y-396) (20,21).…”
mentioning
confidence: 99%
“…Expression of CbpY317F and Cbp knockdown diminishes the amount of Csk within microdomains Cbp, EGFR and Src have been reported to be localized within the microdomains (Lisanti et al, 1994;Smart et al, 1995;Kawabuchi et al, 2000). As shown in Figure 4a, Cbp, EGFR, and Src were all enriched in the same fractions where the microdomain-characteristic protein caveolin-1 was present.…”
Section: Tyr317 Of Cbp Mediates Cbp-csk Associationmentioning
confidence: 85%
“…It has been reported that a point mutation of murine Cbp at the Tyr314 residue abrogated its binding to Csk (Kawabuchi et al, 2000). A construct of human Cbp was generated in which Tyr317, the counterpart of Tyr314 in murine Cbp, was substituted with phenylalanine (CbpY317F).…”
Section: Tyr317 Of Cbp Mediates Cbp-csk Associationmentioning
confidence: 99%
See 1 more Smart Citation